Irrational re-interpretation through series of emotional portraiture inspired by works of Christina Otero and Clara Lieu / Nurfarizah Abdul Rahman and Associate Prof .Jailani Abu Hassan - Nurfarizah, Abdul Rahman; Jailani, Abu Hassan (Universiti Teknologi MARA, Perak, 2019)
Workplaces or studio constitute the important sites where individuals can construct and negotiate their own social identities. Firstly, this paper can illustrate how I construct the identities by using emotion in ways to exploit that specific discursive norm that characterize the identity. Emotion also comprises a valuable component of the linguistic. As the beginning process of making artwork is the process of critical thinking that I apply the concept of mix and match by using Adobe Photoshop. Several images that I pick from Google I use it as my main idea to develop. Furthermore, the idea behind the process of mine involves the sense of self-discovery, curiosity, and emotion that I have along the way and applying these feelings, thoughts into my series of drawing. Ripple human face that I use closely related with my daily life, image that I draw is image that I try to describe my feeling, what I feel, what I go through during my life journey, during the process of making artwork, as honest as I felt that my drawing describe what I go through, how I try to overcome emotion that well off inside myself all this while.